ADAPTING IN-SERVICE TEACHER TRAINING MATERIALS AND ACTIVITIES INTO TEACHING ENGLISH AS A FOREIGN LANGUAGE MATERIALS AS A STUDI PROGRAM LECTURE (A Classroom Action Research at the Group 3, 6th Semester English Education Study Program of STAIN Watampone) - Nirwana Darwis (EKSPOSE, 2018)
The writing aims at finding out of the effectiveness of adapting teacher training materials and activities into teaching English as a foreign language course. The method of this research employed qualitative quantitative classroom action research design which involve eighteen learners of English department education study program of IAIN Bone. The result means that in-service teacher training materials and activities is able to develop the teachers teaching competence when adapting it into teaching English as a foreign language materials.